Pengaruh Faktor Sosial Ekonomi Terhadap Prevalensi Stunting di Indonesia - Elsin Tina; Novya Zulva Riani (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Stunting is a health problem in toddlers that has become an important issue in national development. This study aims to analyze the influence of poverty, maternal education, protein consumption, acces to safe drinking water, and acces to proper sanitation on the prevalence of stunting in Indonesia. The data used is panel data from 34 provinces in Indonesia during 2018-2024, sourced from the Central Statistics Agency and the Indonesian Ministry of Health. The research uses panel dataa regression method with the Random Effect Model (REM). The estimation results found that poverty has a positive and significant effect on stunting prevalence. Maternal education has a negative and significant effect on the prevalence of stunting. However, protein consumption does not have a significant effect on the prevalence of stunting. Acces to safe drinking water has a negative and significant impact on stunting prevalence. Proper sanitation access has a negative and significant effect on the prevalence of stunting in Indonesia. This study emphasizes the importance of optimizing efforts to alleviate poverty, improving women’s education, and enhancing and equalizing acces to clean water and proper sanitation.